let s1, s2 be Real_Sequence; :: thesis: ( ( for m being Nat holds s1 . m = a |^ m ) & ( for m being Nat holds s2 . m = a |^ m ) implies s1 = s2 )

assume that

A2: for n being Nat holds s1 . n = a |^ n and

A3: for n being Nat holds s2 . n = a |^ n ; :: thesis: s1 = s2

for n being Element of NAT holds s1 . n = s2 . n

assume that

A2: for n being Nat holds s1 . n = a |^ n and

A3: for n being Nat holds s2 . n = a |^ n ; :: thesis: s1 = s2

for n being Element of NAT holds s1 . n = s2 . n

proof

hence
s1 = s2
by FUNCT_2:63; :: thesis: verum
let n be Element of NAT ; :: thesis: s1 . n = s2 . n

thus s1 . n = a |^ n by A2

.= s2 . n by A3 ; :: thesis: verum

end;thus s1 . n = a |^ n by A2

.= s2 . n by A3 ; :: thesis: verum